Loss of Adenylyl Cyclase 6 in Leptin Receptor‐Expressing Stromal Cells Attenuates Loading‐Induced Endosteal Bone Formation. (14th October 2020) - Riffault, Mathieu; Johnson, Gillian P; Owen, Madeline M; Javaheri, Behzad; Pitsillides, Andrew A; Hoey, David A
ABSTRACT: Bone marrow stromal/stem cells represent a quiescent cell population that replenish the osteoblast bone‐forming cell pool with age and in response to injury, maintaining bone mass and repair. A potent mediator of stromal/stem cell differentiation in vitro and bone formation in vivo is physical loading, yet it still remains unclear whether loading‐induced bone formation requires the osteogenic differentiation of these resident stromal/stem cells. Therefore, in this study, we utilized the leptin receptor (LepR) to identify and trace the contribution of bone marrow stromal cells to mechanoadaptation of bone in vivo. Twelve‐week‐old Lepr‐cre;tdTomato mice were subjected to compressive tibia loading with an 11 N peak load for 40 cycles, every other day for 2 weeks. Histological analysis revealed that Lepr‐cre;tdTomato + cells arise perinatally around blood vessels and populate bone surfaces as lining cells or osteoblasts before a percentage undergo osteocytogenesis. Lepr‐cre;tdTomato + stromal cells within the marrow increase in abundance with age, but not following the application of tibial compressive loading. Mechanical loading induces an increase in bone mass and bone formation parameters, yet does not evoke an increase in Lepr‐cre;tdTomato + osteoblasts or osteocytes. To investigate whether adenylyl cyclase‐6 (AC6) in LepR cells contributes to this mechanoadaptive response, Lepr‐cre;tdTomato mice were further crossed with AC6 fl/fl mice to generate a LepR + cell‐specific knockout of AC6 . These Lepr‐cre;tdTomato;AC6 fl/fl animals have an attenuated response to compressive tibia loading, characterized by a deficient load‐induced osteogenic response on the endosteal bone surface. This, therefore, shows that Lepr‐cre;tdTomato + cells contribute to short‐term bone mechanoadaptation. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.